2017
DOI: 10.7575/aiac.ijkss.v.5n.3p.56
|View full text |Cite
|
Sign up to set email alerts
|

Race Pattern of Women’s 100-m Hurdles: Time Analysis of Olympic Hurdle Performance

Abstract: Background: For control and effective management of training process in women’s 100-m hurdles event, the coaches, in addition to detailed biomechanical parameters, need also overall, more comprehensive technical parameters, called direct performance descriptors which are used for planning the distribution of an athlete’s efforts over the race. Purpose: The aim of this study was the investigation of the race behavior of elite women sprint hurdlers, on the basis of selected time parameters, and the examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 9 publications
4
11
4
Order By: Relevance
“…Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other. Compared to the previous study (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) ,correlations of the approach run phase, hurdle unit phase, run-in phase were greater in the present study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other. Compared to the previous study (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) ,correlations of the approach run phase, hurdle unit phase, run-in phase were greater in the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…The results indicated that men had significant difference (p-value < 0.01) less time in Run-in than women. The results of current studies highly supported with previous https://www.indjst.org/ studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .Hurdler clearance results revealed that women had Mean/SD (0.28±0.02) significant difference (p-value < 0.01) cross hurdle in less time than men (M/SD=0.35±0.03). Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The most common analysis of the hurdle’s races has been carried out through an evaluation of the hurdle split times (from touchdown to touchdown behind the hurdle), using video recordings with a fixed or panned video-camera both in 110 and 100 m (Muller and Hommel, 1997; Graubner and Nixdorf, 2011; Tsiokanos et al, 2017; Pollitt et al, 2018a,b) as of 60 m hurdles (Walker et al, 2019a,b). López del Amo et al (2018) found that the reaction time and the approach run time were predictors of race performance, however, Tsiokanos et al (2017) did not observed a significant relationship between reaction time and the race performance. Similarly, Tsiokanos et al (2017) determined that the correlation between the intermediate times and final performance was decisive from the fifth hurdle onwards in the 110 m hurdles event ( r = 0.77 – 0.98).…”
Section: Introductionmentioning
confidence: 99%